(untitled) (Technological Innovations Journal, 2022)
The general objective of this article was to record the educational experience of using Google drive as a means to optimize internal communication in a secondary level educational institution, an experience that arises as a result of remote work as a health measure in the face of the Covid-19 pandemic. 19. The qualitative approach applied to education was used, using the case study methodology where the appreciation of four professionals from the Amauta School in the city of Sicuani (Peru) was collected, directly selected according to the inclusion criteria, for this A semi-structured interview was used, taking previous studies as a reference. The categories and subcategories were identified (Google drive: as a repository and applications for internal communication; Internal communication: employment relationship and effectiveness). The work context was collected where the Google drive applications were used in various ways according to the needs. Among the findings, it was detected that it is not the only resource to be used and it is possible to continue looking for other resources with similar benefits; but it has served to insert the teaching team in the technological field. By way of conclusion, the important role of managers who promote different innovations, and the predisposition of teachers to use different resources are highlighted.